2002
DOI: 10.1007/s11661-002-0205-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of amorphous magnesium-rich magnesium-copper and magnesium-nickel alloys

Abstract: Amorphous magnesium-rich alloys Mg y X 1Ϫy (X ϭ Ni or Cu and 0.82 Ͻ y Ͻ 0.89) have been produced by melt spinning. The crystallization kinetics of these alloys have been determined by in situ X-ray diffraction (XRD) and isothermal and isochronal differential scanning calorimetry (DSC) combined with ex situ XRD. Microstructure analysis has been performed by means of transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS). Crystallization of the Mg-Cu alloys at high temperature takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 17 publications
3
38
0
2
Order By: Relevance
“…The upper limit of the amorphization range increases to 34 at.% Cu if the amorphous phase is assumed to have chemical short-range order, but comparison with the experimental amorphization range suggests that chemical short-range order is not well developed in the amorphous alloy. Crystallization of the amorphous alloys will produce a mixture of the stable Mg and CuMg 2 phases [36,37].…”
Section: Copper-magnesiummentioning
confidence: 99%
“…The upper limit of the amorphization range increases to 34 at.% Cu if the amorphous phase is assumed to have chemical short-range order, but comparison with the experimental amorphization range suggests that chemical short-range order is not well developed in the amorphous alloy. Crystallization of the amorphous alloys will produce a mixture of the stable Mg and CuMg 2 phases [36,37].…”
Section: Copper-magnesiummentioning
confidence: 99%
“…From them, the formation enthalpy at 0 K of Mg 6 Pd 0.5 Ni 0.5 has been calculated as À11.5 kJ/mol atoms, a result which confirms the tendency to destabilization introduced by the substitution of Pd by Ni (D f H 0 0 (Mg 6 Pd) ¼ À21.8 kJ/mol atoms). It should be remembered that Mg 6 Ni is isomorphous to Mg 6 Pd but it is a metastable phase only formed either by low-temperature annealing of amorphous melt-spun ribbons [20] or under very high hydrogen pressures [17]. The enthalpy change of reaction (1) can be calculated from the enthalpy of formation of the several phases entering in reactions (2)-(5).…”
Section: Enthalpy Of Reactionmentioning
confidence: 99%
“…Previous investigations have shown that Mg 6 Ni compound, isomorphous to Mg 6 Pd, can be prepared in a metastable state by low-temperature annealing of melt-spun amorphous ribbons [20]. Mg 6 Ni transforms into a two-phase alloy Mg þ Mg 2 Ni above 473 K. Hydrogenation properties of metastable Mg 6 Ni and related compounds have been reported [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Glass formation in the Cu-Mg system has been extensively studied in the past [36,37] and a glass forming range (GFR) appears around the eutectic between hcp-Mg and CuMg 2 phases. The Cu-Mg equilibrium phase diagram has been assessed by several authors and the most recent thermodynamic description, carried out by Liang et al [38] as part of the modelling of the ternary Cu-Mg-Zn system, has been taken as a starting point.…”
Section: Cu-mgmentioning
confidence: 99%